The Role of Arabic in Islamic Education - Ayu Sekarsari; Addin Abdillah; Anisa Eka Putri Aulia; Afifa Mawada (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Arabic language plays a crucial role in Islamic education, primarily because all Islamic teachings, including the Quran and Hadith, are in Arabic. This language is fundamental for facilitating understanding of the holy scriptures and the Prophet's traditions. The role of Arabic is vital in the daily lives of Muslims, such as in prayer and supplication. In Islamic boarding schools (pesantren), Arabic language flourishes, is considered special, and possesses distinct characteristics compared to other languages. This study highlights the importance of Arabic proficiency as a foundation for delving deeper into religious teachings with greater focus and shaping the identity of students (santri). Research employs the method of library research with techniques of content analysis and constant comparative analysis. Good Islamic education, both formal and informal, imparts religious knowledge based on the Quran and Hadith, facilitating the formation of strong morals and faith. Arabic, as an international language and the language of the Quran, is taught in various schools and madrasahs to achieve basic language competence, including listening, speaking, reading, and writing. Methods for learning Arabic are divided into traditional/classical and modern approaches, each emphasizing communication within cultural contexts and practical everyday skills. In Islamic education, Arabic language holds an urgent role as the primary source of religious teachings. Scholars like Dr. Muhammad Saed Abdul Rahman, Dr. Abul Hasan Ali Nadwi, and Prof. Mustansir Mir emphasize that Arabic is not just a means of communication but also a key to deepening understanding of Islam, preserving its intellectual and spiritual heritage.